Coronavirus Disease 2019 (COVID-19) Prevalences Among People Experiencing Homelessness and Homelessness Service Staff During Early Community Transmission in Atlanta, Georgia, April–May 2020. (8th September 2020) - Yoon, Jane C; Montgomery, Martha P; Buff, Ann M; Boyd, Andrew T; Jamison, Calla; Hernandez, Alfonso; Schmit, Kristine; Shah, Sarita; Ajoku, Sophia; Holland, David P; Prieto, Juliana; Smith, Sasha; et al.
Abstract: Background: In response to reported coronavirus disease 2019 (COVID-19) outbreaks among people experiencing homelessness (PEH) in other US cities, we conducted multiple, proactive, facility-wide testing events for PEH living sheltered and unsheltered and homelessness service staff in Atlanta, Georgia. We describe the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) prevalence and associated symptoms, and review shelter infection prevention and control (IPC) policies. Methods: PEH and staff were tested for SARS-CoV-2 by reverse transcription polymerase chain reaction (RT-PCR) during 7 April–6 May 2020. A subset of PEH and staff was screened for symptoms. Shelter assessments were conducted concurrently at a convenience sample of shelters using a standardized questionnaire. Results: Overall, 2875 individuals at 24 shelters and 9 unsheltered outreach events underwent SARS-CoV-2 testing, and 2860 (99.5%) had conclusive test results. The SARS-CoV-2 prevalences were 2.1% (36/1684) among PEH living sheltered, 0.5% (3/628) among PEH living unsheltered, and 1.3% (7/548) among staff. Reporting fever, cough, or shortness of breath in the last week during symptom screening was 14% sensitive and 89% specific for identifying COVID-19 cases, compared with RT-PCR. Prevalences by shelter ranged 0–27.6%. Repeat testing 3–4 weeks later at 4 shelters documented decreased SARS-CoV-2 prevalences (0–3.9%). Of 24 shelters, 9 completed shelter assessments and implemented IPC measures as part of the COVID-19 response. Conclusions: PEH living in shelters experienced a higher SARS-CoV-2 prevalence compared with PEH living unsheltered. Facility-wide testing in congregate settings allowed for the identification and isolation of COVID-19 cases, and is an important strategy to interrupt SARS-CoV-2 transmission. Abstract : Facility-wide severe acute respiratory syndrome coronavirus 2 testing revealed higher infection rates among homeless people living sheltered than unsheltered, and allowed for identification and isolation of infected individuals. Repeat testing in 4 facilities demonstrated decreasing coronavirus disease 2019 prevalences.